PENGARUH PENDAPATAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN EKONOMI KELAS X TAHUN AJARAN 2015/2016 SMA NEGERI 7 PEKANBARU - Fitrah, Hidayatul; Nas, Sakdanur; Syabrus, Hardisyem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: Abstract: low academic achievement is a prayer one problem encountered frequently kita hearts' community kita and singer problems are almost in whole school neither itu basic, intermediate even in higher education. As the nation yang ingin maju, kita also of course wants quality kita education can be meningkat.tetapi problem is that the issue of education singer very complex the subscription with hal different, from the national policy issues government operations until with issue concerning each learners. Between criteria of success in education as desired is relevant itu needs against society and national development, itu translated and elaborated hearts shape destination and education goals that can be used as a standard or benchmark to review measures how much that successful business education. Family status variables such as the income a very influential families against the smooth process of the child's learning. The family is the first social institution which is known by the child and family singers hearts can be embedded attitudes that can be affecting further child development. The family is responsible for the review of funds providing education needs children. Family (parents) that had the higher revenues will not hearts many have difficulty fulfilling the school needs kids, parents differ the revenue was low. Factors - these factors on is essentially a series of findings interaction the shaping achievement studied economics. To review acquire learning achievement economy the good, so students must achieve good value anyway. Singer study aims to determine the influence of revenue review of parents against students learning achievements. Singer research conducted SMA NEGERI 7 PEKANBARU on the tin 72 the research sample using method location probability sample. Data analysis techniques used the hearts research singer is simple linear regression analysis techniques. Based on the findings of that study tin income parents effect on student achievement by 0087. Keywords: Income Parents and Student Achievement.